An Interactive Heuristic Approach for Multi-Objective Integer-Programming Problems - Gabbani, Diaa; Magazine, Michael (The Journal of the Operational Research Society, 1986)
An interactive approach to solve the multi-objective integer-programming problem heuristically is described. The approach consists of two main parts. The first is an algorithm to guide the search for a set of weights to the objective functions which would produce the solution most preferred by the decision-maker given a linear utility function. The search area is successively decreased through an interaction process, with the decision-maker using a selection and contraction method. During each stage of this algorithm, a number of single integer-programming problems are solved heuristically. The motivation for this approach, along with some computational experimentation, is provided.